Low and fixed dose of hydroxyurea is effective and safe in patients with HbSβ+ thalassemia with IVS1‐5(G→C) mutation. Issue 6 (24th December 2014) - Dehury, Snehadhini; Purohit, Prasanta; Patel, Siris; Meher, Satyabrata; Kullu, Bipin Kishore; Sahoo, Lulup Kumar; Patel, Nayan Kumar; Mohapatra, Alok Kumar; Das, Kishalaya; Patel, Dilip Kumar
<x xml:space="preserve">Abstract</x> Background Despite compelling evidence that hydroxyurea is safe and effective in sickle cell disease, it is prescribed sparingly due to several barriers like knowledge gaps in certain genotypes, apprehension about its safety and toxicity, and limited resources. We undertook this study to find out the efficacy and safety of HU in patients with HbSβ+‐thalassemia with IVS1–5(G→C) mutation. Procedure We registered 318 patients with HbSβ+‐thalassemia with IVS1–5(G→C) mutation. Of these, 203 were enrolled for hydroxyurea treatment at a low and fixed dose of 10 mg/kg/day. One hundred four patients (Group‐I: 37 children and Group‐II: 67 adults) with ≥2 years of hydroxyurea treatment were studied. Results The rate of vaso‐occlusive crises, requirement of blood transfusion and rate of hospitalization reduced from 3 to 0.5, 1 to 0 and 1 to 0 in Group‐I and 3 to 0, 1 to 0 and 0.5 to 0 in Group‐II respectively after HU therapy (P < 0.0001). %HbF level, hemoglobin, MCV and MCH increased significantly, whereas HbS, WBC, platelet count, serum‐bilirubin and LDH levels decreased significantly after HU therapy. It has been observed that along with fairly subtle hematological changes following HU therapy, there was a substantial clinical improvement occurred in these patients. Transient myelotoxicity was observed in 4.8%. There was minimal gonadal toxicity without affecting reproductive function. Conclusion In view of easy affordability, better acceptability, minimal toxicity, the need of infrequent monitoring and its potential effectiveness, low and fixed dose of hydroxyurea is suitable for treatment of patients with HbSβ+‐thalassemia in resource poor setting. Pediatr Blood Cancer 2015;62:1017–1023. © 2014 Wiley Periodicals, Inc.